OPTIMALISASI PERTUMBUHAN DAN PRODUKSI TANAMAN PAKCOY (Brassicca rapaL) MELALUI APLIKASI BEBERAPA DOSIS PUPUK BOKASHI - Vivonda, Tri '; ', Armaini '; Yoseva, Sri ' (Jurnal Online Mahasiswa (JOM) Bidang Pertanian, 2016)
ABSTRACT The research was aimed to know influence of bokashi fertlizer to get the growth and production of pakcoy and to get the effective dose of bokashi fertilizer. The research was conducted at the experimental farm of Faculty of Agriculture University of Riau from April 2016 to May 2016. The study was carried out experiments using a Completely Randomized Design (CRD) consisting of one Factor that bokashi fertilizer with 5 treatments and 4 replications. The observation made are measuring of plant height, number of leaves, fresh wieght of plant on plots, fresh weight of plant, heavy of plant for consumption and ratio heading roots. The results showed that given of some dose bokashi fertilizer influencing pakcoy on all parameters, and given of 3 ton/ha bokashi fertilizer is the most effective dose for the growth and production of pakhcoy. Keywords: pakchoy, bokashi fertilizer